Programmable Nuclease-Based Integration into Novel Extragenic Genomic Safe Harbor Identified from Korean Population-Based CNV Analysis - Eun-Seo Lee; Sanghoon Moon; Kwaku Dad Abu-Bonsrah; Yun Kyoung Kim; Mi Yeong Hwang; Young Jin Kim; Seokjoong Kim; Nathaniel S. Hwang; Hyongbum Henry Kim; Bong-Jo Kim (Molecular Therapy: Oncolytics, 2019)
Here, we found two genomic safe harbor (GSH) candidates from chromosomes 3 and 8, based on large-scale population-based cohort data from 4,694 Koreans by CNV analysis. Furthermore, estimated genotype of these CNVRs was validated by quantitative real-time PCR, and epidemiological data examined no significant genetic association between diseases or traits and two CNVRs. After screening the GSH candidates by in silico approaches, we designed TALEN pairs to integrate EGFP expression cassette into human cell lines in order to confirm the functionality of GSH candidates in an in vitro setting. As a result, transgene insertion into one of the two loci using TALEN showed robust transgene expression comparable to that with an AAVS1 site without significantly perturbing neighboring genes. Changing the promoter or cell type did not noticeably disturb this trend. Thus, we could validate two CNVRs as a site for effective and safe transgene insertion in human cells. Keywords: genome editing, TALEN, safe harbor, copy number variation region